Dietary Factors Moderate the Relation between Groundwater Iron and Anemia in Women and Children in Rural Bangladesh - Wendt, Amanda S (Curr Dev Nutr, 2019)
BACKGROUND: Anemia affects ∼1.6 billion people worldwide, often owing to iron deficiency. In Bangladesh, high levels of anemia have been observed alongside little iron deficiency. Elevated concentrations of groundwater iron could constitute a significant source of dietary iron. OBJECTIVE: We aimed to quantify the effect of groundwater iron on anemia in nonpregnant women and young children in Bangladesh, taking into account dietary factors that may affect iron absorption. METHODS: We analyzed data on 1871 nonpregnant women and 987 children (6–37 mo) from the 2015 baseline survey of the Food and Agricultural Approaches to Reducing Malnutrition cluster-randomized trial in Sylhet, Bangladesh. We used logistic regression with robust standard errors to assess effects of self-reported groundwater iron, dietary intake, and sociodemographic characteristics on anemia, considering interactions between groundwater iron and dietary factors. RESULTS: Groundwater iron presence was associated with less anemia in women (OR: 0.74; 95% CI: 0.60, 0.90) and children (OR: 0.58; 95% CI: 0.44, 0.76). This effect was modified by dietary factors. In women, the effect of groundwater iron on anemia was stronger if no vitamin C–rich or heme-iron foods were consumed, and there was a clear dose–response relation. In children, intake of vitamin C–rich foods strengthened the effect of groundwater iron on anemia, and there was no evidence for interaction by intake of iron-rich foods. CONCLUSIONS: Heme-iron and vitamin C consumption reduced the effect of groundwater iron on anemia among women but not children in Bangladesh, which may be due to higher levels of iron deficiency and lower levels of iron intake among children. Vitamin C consumption appears to enhance iron absorption from groundwater in children and they may thus benefit from consuming more vitamin C–rich fruits and vegetables. Even among women and children consuming heme-iron or vitamin C–rich foods and groundwater iron, anemia prevalence remained elevated, pointing to additional causes of anemia beyond iron deficiency. This trial was registered at clinicaltrials.gov as NCT02505711.